Hubungan Faktor Pekerjaan, Pendapatan Keluarga, dan Dukungan Tokoh Masyarakat dengan Kepemilikan Jamban - Yulizar, Yulizar; Santosa, Heru; Nurmaini, Nurmaini; Indirawati, Sri Malem; Pramesona, Bayu Anggileo (Jurnal Kesehatan, 2022)
Based on BPS data in 2017, around 25 million Indonesians still defecate openly. Many factors influence the ownership of latrines, but research related to factors of employment, family monthly income, and support from community leaders for latrine ownership in Aceh Barat Daya Regency is still rarely done. This study aimed to determine the relationship between employment, family monthly income, and support from community leaders on latrine ownership. This cross-sectional study with a sample of 100 respondents who were randomly selected and scattered in sub-districts was conducted in the urban area of Aceh Barat Daya Regency, Nanggroe Aceh Darussalam province. Questionnaires related to respondent characteristics, employment, family monthly income, and support from community leaders, as well as latrine ownership, were collected directly by the researchers through face-to-face interviews from September-October 2021. The statistical tests used were Chi-Square and Mann-Whitney with a significance level of p-value<0.05. The results showed that there was no significant relationship between employment (p-value=0.604), family monthly income (p-value=0.118), and support from community leaders (p-value=0.615) on latrine ownership. In conclusion, there is no relationship between employment factors, family monthly income, and support from community leaders for latrine ownership in Aceh Barat Daya District, Nanggroe Aceh Darusalam province. Village to district governments can offer policies that ensure that every house, owned or rented, must be equipped with proper sanitation facilities. This program can work well if it involves the community, local stakeholders, and landowners.